F18 Promiscuous Epitope of Acr1 Protein of Mycobacterium tuberculosis Induces the Secretion of IL-10 and Tregs but Not IL-6 - Lamba, Taruna; Prajapati, Shivank; Chowdhury, Arnab; Bandyopadhyay, Anupam; Agrewala, Javed N. (Protein and Peptide Letters, 2025)
IntroductionMycobacterium tuberculosis (Mtb) is a Gram-positive bacterium that causes tuberculosis (TB). It remains viable for extended periods within host macrophages by entering a dormant state. Alpha crystallin 1 (Acr1) is a 16 kDa protein of Mtb and is reported to be highly upregulated in latent TB. Acr1 suppresses the host’s immune system by impairing the differentiation and maturation of dendritic cells and macrophages. We hypothesize that Mtb judiciously utilizes its Acr1 protein to paralyse the immune system of the host by inducing the release of IL-10 and generating an immunosuppressive environment.MethodsWe employed in silico tools to identify highly promiscuous, IL-10-inducing and IL-6-non-inducing epitopes of Mtb. Moreover, the selected epitope was synthesized and tested for its suppressive activity and generation of Tregs.ResultsWe identified the presence of a specific epitope in Acr1 (F18) that is responsible for bolstering the release of IL-10 and Tregs through in silico tools and verified the activity by in vitro assays. In hPBMCs, the F18 epitope could suppress the proliferation of CD4 T cells stimulated with PHA and expand the pool of Tregs in a dose-dependent manner.DiscussionThe F18 epitope from Mtb’s Acr1 protein promotes IL-10 and Treg responses without triggering pro-inflammatory IL-6, suggesting its probable immunoregulatory role. While it holds potential for treating autoimmune diseases, its impact on infection in tuberculosis should be further investigated.ConclusionOur findings suggest that the F18 epitope induces IL-10 production and Treg differentiation while inhibiting CD4+ T cell proliferation and IL-6 secretion, thereby promoting an immunosuppressive environment. Furthermore, this study highlights the possible role of Acr1 and its immunosuppressive epitope F18 as therapeutic agents for inducing suppressive Tregs, which may help in the management of autoimmune diseases.
Keywords: autoimmunity